1995
DOI: 10.1021/ic00122a009
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Oxidation of HSO3- by O2. 1. The Uncatalyzed Reaction

Abstract: The reaction between S(1V) and 0 2 in aqueous solution is of importance because of its involvement in flue gas desulfurization processes and in acid rain formation. Despite considerable research, a complete mechanism for the reaction has not been established. In this work a detailed study of the uncatalyzed reaction in the region of pH 4.5 has been carried out. The overall rate law was found to be -d[02]/dt = kobs [HS03-]2[H+]-2[02]o with kobs of 3.6 x lo6 M s-' at 25 "C and ionic strength 0.05 M. The yield of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 0 publications
4
73
0
Order By: Relevance
“…1) by adding different concentrations of Co 2+ -ions. The Orange II photobleaching traces present a trend similar to the trend observed in processes involving a radical chain branching mechanism [22,23]. Fig.…”
Section: Effect Of the Cobalt And Oxone Concentrations On The Photoblsupporting
confidence: 75%
See 1 more Smart Citation
“…1) by adding different concentrations of Co 2+ -ions. The Orange II photobleaching traces present a trend similar to the trend observed in processes involving a radical chain branching mechanism [22,23]. Fig.…”
Section: Effect Of the Cobalt And Oxone Concentrations On The Photoblsupporting
confidence: 75%
“…Oxone has been successfully used in dark and photochemical reactions [12] like: olefin epoxydations [13,14], chemiluminescence detection of oxidative processes [15] and diverse sulfate oxidation reactions [16]. Catalytic decomposition of oxone (PMS) in the presence of some semiconductors WO 3 , Bi 2 O 3 and Fe 2 O 3 [17,18] and metallic-ions like Mn 2+ [19], Cu 2+ [20] and Co 2+ [21,22] has also been recently reported.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al [37] reported that radical mechanism operate in those reaction in which the inhibition parameters lies 10 3 -10 4 In the present study the value of inhibition parameter for uncatalysed and Ag(I) catalysed autoxidation of S(IV) by anilineare found to be in the range 10 3 -10 4 These values are in the same range as reported by Gupta et al [37] This is strongly support the radical mechanism in the present case too based on the observed results. The free radical mechanism is very complex, the present work close to the experimental condition of Connick et al [38]. …”
Section: Hso H Sosupporting
confidence: 85%
“…2), the value of 3.2 9 10 3 L mol -1 s -1 for k Fe at 30°C was found. Ethanol is a well-known inhibitor for sulfur(IV) autoxidation reactions catalyzed by iron(III) and other metal ions [11,[24][25][26][27]. In this study, the presence of ethanol led to the introduction of an induction period and decrease in the reaction rate, so much so that at 8.5 9 10 -3 mol L -1 ethanol, the reaction was completely seized ( [ethanol] was linear (Fig.…”
Section: Resultsmentioning
confidence: 74%